Drug Testing and Pretrial Misconduct: An Experiment on the Specific Deterrent Effects of Drug Monitoring Defendants on Pretrial Release - Britt, Chester L. - (Journal of research in crime and delinquency, 1992)
Presents an experimental data from Pima County and Maricopa County, Arizona, where defendants are assigned to drug monitoring and nonmonitoring groups. Experimental design; How the design of the experimental study in Maricopa was identical to that in Pima; Findings of the experiment; Conclusions